User experiences on implementation of patient reported outcome measures (PROMs)in a Haematological outpatient clinic - Stine Thestrup Hansen; Mette Kjerholt; Sarah Friis Christensen; John Brodersen; Bibi Hølge-Hazelton (SpringerOpen, 2020)
Abstract Background PROMs can help healthcare professionals gain an improved understanding of patients' physical burdens, functional levels, and (health-related) quality of life throughout disease and medical treatment. The aim of this study was to investigate the barriers and potential opportunities PROMs may present in a haematological outpatient clinic from three different perspectives: patients, nurses and haematologists. Methods The present study synthesizes three previously published studies that separately explored the experiences of patients, nurses and haematologists when implementing PROMs. The studies were all guided by the qualitative methodology Interpretive Description, including a focused ethnographic approach, to develop implications for future practice. Results The overall themes that emerged from the analysis were "Structural similarities influence the adoption of PROMs" and "Different perspectives on the potential of PROMs." Conclusion Across the different user groups in the haematological outpatient clinic, the use of PROMs was thwarted due to an unquestioned commitment to biomedical knowledge and the system's rationality and norms: PROM data was not used in patient consultations. Nurses and haematologists expressed different preferences related to potential future PROMs and different objectives for PROMs in clinical practice. From the different perspectives of the patients, nurses and haematologists, PROMs were not compatible with clinical practice. Further research is recommended to develop PROMs validated for use in haematological outpatient clinics. Moreover, implementation strategies adjusted to the structural barriers of the system are crucial.